PENERAPAN SUPERVISI KLINIS UNTUK MENINGKATKAN MUTU PROSES PEMBELAJARAN SDN 06 KOTO GADANG GUGUK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Zulbakti Zulbakti (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
This research is done at elementry school No 06 Koto Gadang Guguk Kecamatan Gunung Talang Kabupaten Solok regency, that the competence of teacher got difficult in planning and doing learning process in the classroom. The action research toward to the teachers elementry school No 06 Koto Gadang Guguk Kecamatan Gunung Talang by observing class in klinis suvervition. To improve teachers ability in doing learning process. Through two circles. The step are planning, teaching and observing and reflection. Tow achieevement teacher ability in teaching learning process. To improvement we can see to teacher of class 1 to vi. From the result of the mark from the students. So this action research we can conclude that observing classroom in clinical suvervision is very effective to increase quality of learning process.